Laminate and manufacturing method of laminate

The low refractive index film with defined void conditions in its first layer and strategic layering improves antireflection performance and mechanical stability, addressing the limitations of existing films.

JP2024174992AInactive Publication Date: 2024-12-17NIPPON SHEET GLASS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024157431
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2024-09-11
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing antireflection films, such as those described in Patent Documents 1 and 2, lack clarity in the quantitative state of voids near the glass substrate and have high binder fill rates in certain layers, leading to suboptimal antireflection performance.

Method used

A low refractive index film comprising a first layer with specific void conditions (number density and void ratio) and a second layer, where the first layer is closer to the substrate, with a thickness less than half the total film and containing hollow particles and a binder, achieving a refractive index between 1.01 and 1.30.

Benefits of technology

The proposed film design enhances antireflection performance by ensuring a low refractive index and mechanical stability, reducing the risk of cracking and improving light transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174992000001_ABST
    Figure 2024174992000001_ABST
Patent Text Reader

Abstract

To provide a new low refractive index film that is advantageous from the viewpoint of showing a high reflection prevention performance.SOLUTION: A low refractive index film 10 has at least a first layer 11 and a second layer 12. The first layer 11 is adjacent to a base material 20. The low refractive index film 10 has a refractive index of 1.01 or higher and 1.30 or lower. Each of the first layer 11 and the second layer 12 contains a hollow particle 13 and a binder 14. The first layer 11, for example, satisfies at least one of the following conditions (I) and (II): (I) a number density ρv1 of a void 15 having a cross-sectional area of 1,000 nm2 or more in a cross section of the first layer 11 is 5 / μm2 or more and 100 / μm2 or less; and (II) a ratio of a cross-sectional area of the void 15 in a cross section relative to a total area of the cross section of the first layer 11 is 5% or more and 70% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a low refractive index film, a laminate, an optical element, a windbreak material, and a display device. [Background technology]

[0002] Conventionally, anti-reflective coatings are known that suppress the reflection of light from the surface of a transparent article or substrate by coating the article or substrate with a material having a predetermined refractive index. In particular, in fields and applications such as optical elements such as lenses and filters, windows and structural materials used in buildings, windshields for automobiles, and shields such as helmets and goggles, it is important to form an anti-reflective coating on the surface in order to suppress the reflected light from the surface and increase the amount of light transmitted through the article or substrate. For example, the reflectance of one surface of glass is usually about 4 to 5%. Therefore, in an article made of plate-like glass, the overall reflectance considering the reflection on the front surface and the reflection on the back surface can be 8 to 10%. The reflected light from the surface of a glass lens used with an imaging device such as a camera is repeatedly reflected or refracted by the device or by the surface of other lenses, which can cause undesirable phenomena such as ghosts or flares. Therefore, it is essential to form an anti-reflective coating on the surface of an article or substrate that performs functions such as the transmission or refraction of light, and suppress the reflection on the surface.

[0003] According to the theory of light reflection, it is expected that the reflected light is easily reduced by making the refractive index of the material constituting the anti-reflective film smaller than the refractive index of the substrate to be coated (ideally the square root of the refractive index of the article to be coated). However, there is no material made of a single substance with a sufficiently low refractive index, and conventionally, there are multilayered films in which multiple layers with different refractive indexes are laminated, and films containing substances such as hollow particles that have the effect of reducing the refractive index, thereby reducing the refractive index of the entire film, which are called low refractive index films.

[0004] For example, Patent Document 1 describes an anti-reflection film in which hollow particles are bound with a binder. The binder contains particles with a cross-sectional area of ​​1000 nm 2 Voids and cross-sectional areas less than 1000 nm 2 The binder contains voids with a cross-sectional area of ​​1000 nm or more. 2 The number of voids above is calculated based on the cross-sectional area of ​​the binder of 1 μm 2 10 pieces / μm 2 In the embodiment, an anti-reflection film is formed on a glass substrate BK7, and the refractive index of the anti-reflection film is 1.27.

[0005] Patent Document 2 describes an optical element having an anti-reflection film formed on a substrate. This anti-reflection film includes a low refractive index layer formed by bonding hollow particles with voids inside with a binder. The low refractive index layer is composed of a first layer as the outermost layer and a second layer adjacent to the first layer and located on the substrate side. The binder filling rate in the first layer is lower than the binder filling rate in the second layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2012-108320 A [Patent Document 2] JP 2013-033124 A Summary of the Invention [Problem to be solved by the invention]

[0007] According to Patent Document 1, the quantitative state of the voids in the anti-reflection film in the portion located near the glass substrate BK7 is unclear. On the other hand, according to Patent Document 2, the binder filling rate in the second layer is high, and there is no mention of the existence of voids in the second layer. For this reason, the refractive index of the second layer tends to be relatively high.

[0008] In view of these circumstances, there is room for reexamination from the viewpoint of improving antireflection performance of the techniques described in Patent Documents 1 and 2. Therefore, the present invention provides a new low refractive index film that is advantageous from the viewpoint of exhibiting high antireflection performance. [Means for solving the problem]

[0009] The present invention relates to A low refractive index film having at least a first layer and a second layer adjacent to the first layer, A refractive index of 1.01 or more and 1.30 or less, each of the first layer and the second layer contains hollow particles and a binder; the first layer has a thickness that is half or less than the thickness of the low refractive index film and is 200 nm or less; The first layer provides a low refractive index film having voids that satisfy at least one of the following conditions (I) and (II). (I) 1000 nm in the cross section of the first layer 2 The number density of the voids having a cross-sectional area of ​​5 / μm 2 More than 100 / μm 2 The following is the result. (II) The ratio of a cross-sectional area of ​​the void in the cross section to an area of ​​the cross section of the first layer is 5% or more and 70% or less.

[0010] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The low refractive index film includes a substrate and the low refractive index film. A laminate is provided in which the first layer is closer to the substrate than the second layer. Effect of the Invention

[0011] The above-mentioned low refractive index film is advantageous in terms of exhibiting high antireflection performance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the laminate according to the present invention. [Figure 2A]FIG. 2A is a cross-sectional view showing another example of the laminate according to the present invention. [Figure 2B] FIG. 2B is a cross-sectional view showing still another example of the laminate according to the present invention. [Figure 2C] FIG. 2C is a cross-sectional view showing still another example of the laminate according to the present invention. [Figure 2D] FIG. 2D is a cross-sectional view showing still another example of the laminate according to the present invention. [Diagram 3] FIG. 3 is a scanning transmission electron microscope (STEM) photograph showing a cross section of the laminate according to Example 1. As shown in FIG. [Figure 4] FIG. 4 is a STEM photograph showing a cross section of the laminate according to Example 1, in which voids are colored black. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. Note that the following description is for illustrative purposes only, and the present invention is not limited to the following embodiment. In this specification, "anti-reflection" refers to a function of preventing reflection of light from a surface, or, even if reflection does not disappear, to a function of reducing reflection compared to a case where there is no anti-reflection structure, and "film" can be understood as synonymous with film, coating, and layer.

[0014] As shown in FIG. 1, the low refractive index film 10 is a film formed along the surface of the substrate 20. The low refractive index film 10 includes a first layer 11 and a second layer 12. The first layer 11 is located proximal to the substrate 20 in the thickness direction of the low refractive index film 10. The second layer 12 is adjacent to the first layer 11 in the thickness direction of the low refractive index film 10 and is located distal to the substrate 20. The low refractive index film 10 has a refractive index of 1.01 or more and 1.30 or less. In this specification, the term "refractive index" means an absolute refractive index, and corresponds to, for example, a measured value at 25° C. using the D line of sodium. The refractive index of the low refractive index film 10 can be determined, for example, by measurement according to reflectance spectroscopy.

[0015] The term "substrate" refers to an article or a part of an article that is coated with a low refractive index film or an anti-reflection film. The term "substrate" is, but is not limited to, optical elements such as lenses, mirrors, prisms, diffusers, flat microlens arrays, polarizers, diffraction gratings, holograms, light modulation elements, light deflection elements, and filters (including acousto-optical elements), solid-state imaging devices, windows or windshields of buildings or automobiles, light-transmitting shields such as helmets and goggles, or display devices such as displays and screens. The coating surface of the "substrate" may be flat, curved, or uneven.

[0016] As shown in FIG. 1, each of the first layer 11 and the second layer 12 contains hollow particles 13 and a binder 14. The first layer 11 has a thickness that is half or less than the thickness of the low refractive index film 10 and is 200 nm or less. The first layer 11 has voids 15 so as to satisfy at least one of the following conditions (I) and (II). Note that the voids 15 exist inside or at the interface of the low refractive index film 10 and are spaces that are not occupied by the hollow particles 13 and the binder 14. For example, the internal space of the hollow particles 13 does not fall under the category of voids 15. The voids 15 contain, for example, air. (I) 1000 nm at cross section S1 of first layer 11 2 The number density ρv1 of voids 15 having a cross-sectional area of ​​5 / μm 2 More than 100 / μm 2 The following is the result. (II) The ratio (Av1 / At1) of the cross-sectional area (Av1) of the voids 15 present in the cross section S1 of the first layer 11 to the area (At1) of the cross section S1 is 5% or more and 70% or less.

[0017] When the first layer 11 satisfies at least one of the conditions (I) and (II), the quantitative state of the voids 15 in the first layer 11 becomes a desired state, and the first layer 11 tends to have a low refractive index in the low refractive index film 10. As a result, the low refractive index film 10 tends to exhibit high antireflection performance. The voids 15 can be formed inside the first layer 11 or at the interface between the low refractive index film 10 and another member.

[0018] Regarding condition (I), "1000 nm 2 The "void 15 having a cross-sectional area of ​​1000 nm or more" refers to a void 15 having a cross-sectional area of ​​1000 nm or more determined by the boundary between the void 15 and the material surrounding the void 15 in the cross section S1. 2 In order to obtain the number density ρv1, a region surrounded by a rectangle having a length (width) of 1000 nm (1 μm) along the surface of the substrate 20 and a height corresponding to the thickness d1 of the first layer 11 is defined as a cross section S1, and the number density ρv1 of the first layer 11 is calculated by dividing the number density ρv1 of the first layer 11 by the number density ρv1 of the first layer 11. 2 The number of voids 15 having a cross-sectional area of ​​5 / μm is counted. The number is divided by the area At1 of the cross section S1 to obtain the number density ρv1. When obtaining the number density ρv1, voids that are completely contained within the region of the cross section S1, voids in which part of the surface of the substrate or underlayer is part of the boundary, and voids that are only partially contained in the cross section S1 are also counted. 2 By satisfying the above, the first layer 11 in the low refractive index film 10 tends to have a low refractive index. In addition, even if there is a large difference between the expansion coefficient of the substrate 20 and the expansion coefficient of the low refractive index film 10, the risk of cracks or splitting occurring in the low refractive index film 10 due to temperature changes is likely to be reduced. The number density ρv1 is preferably 6 / μm 2 More preferably, 8 / μm 2 More preferably, it is 10 / μm or more. 2 The number density ρv1 is 100 / μm 2 By being equal to or less than 99 / μm, the low refractive index film 10 is likely to have a desired mechanical strength. In addition, it is likely to prevent the scattering of incident light such as visible light from becoming large, and it is easy to keep the haze of an article provided with the low refractive index film 10 low. The number density ρv1 is preferably 99 / μm 2 less than 90 / μm, more preferably 2 or less, and more preferably 85 / μm 2 The number density ρv1 is 75 / μm 2 It may be less than 50 / μm 2 It may be the following.

[0019] Regarding condition (II), the ratio (Av1 / At1) expressed as a percentage is also called the void fraction Vv1 [%]. When calculating the void fraction Vv1, 2 The sum of the areas of the voids 15 having the above cross-sectional area is Av1. When calculating the sum of the areas of the voids 15, Av1 is calculated by taking into consideration the area of ​​the voids completely contained within the region of the cross section S1, and the area of ​​the part of the voids only partially contained within the region of the cross section S1. When the void fraction Vv1 is 5% or more, the first layer 11 in the low refractive index film 10 is likely to have a low refractive index. In addition, even if the difference between the expansion coefficient of the substrate 20 and the expansion coefficient of the low refractive index film 10 is large, the risk of cracks or splitting occurring in the low refractive index film 10 due to temperature changes is likely to be reduced. The void fraction Vv1 is preferably higher than 5%, more preferably 9% or more, and even more preferably 10% or more. When the void fraction Vv1 is 70% or less, the low refractive index film 10 is likely to have the desired mechanical strength. The void fraction Vv1 is preferably lower than 70%, more preferably 65% ​​or less. The void fraction Vv1 may be 50% or less, or may be 30% or less.

[0020] When the first layer 11 satisfies the above condition (I), the number density ρv1 is, for example, 1000 nm 2 This is greater than the number density ρv2 of the voids 15 having a cross-sectional area of ​​1000 nm (1 μm) or more. This makes it easier for the first layer 11 in the low refractive index film 10 to have a low refractive index. When determining the number density ρv2, in the cross section of the laminate including the second layer 12, the number density ρv2 of the voids 15 having a cross-sectional area of ​​1000 nm (1 μm) or more that exists within a cross section S2 surrounded by a rectangle having a length (width) of 1000 nm (1 μm) along the surface of the substrate 20 and a height corresponding to the thickness d2 (=dt-d1) of the second layer 12 is calculated. 2The number of voids 15 having a cross-sectional area of ​​1000 nm or more is counted. The number is divided by the area At2 of the cross section S2 to obtain the number density ρv2. When obtaining the number density ρv2, in addition to voids completely contained within the region of the cross section S2, voids in which a part of the surface of the second layer 12 that is in contact with the first layer 11 and the surface facing the first layer 11 are part of the boundary, and voids that are only partially contained within the region of the cross section S2 are also counted. 2 The sum of the areas of voids 15 having the above cross-sectional area is defined as Av2. When calculating the sum of the areas of voids 15, Av2 is calculated taking into account the area of ​​voids that are completely contained within the region of cross section S2, and for voids that are only partially contained within the region of cross section S2, Av2 is calculated taking into account the area of ​​the part that exists within the region of cross section S2.

[0021] When the first layer 11 satisfies the above condition (II), the ratio (Av1 / At1) is, for example, higher than the ratio (Av2 / At2). The ratio (Av2 / At2) is expressed as a percentage of the ratio of the cross-sectional area Av2 of the voids 15 present in the cross section S2 of the second layer 12 to the total area At2 of the cross section S2 of the second layer 12 having a length of 1000 nm extending along the surface of the substrate 20. This makes it easier for the first layer 11 in the low refractive index film 10 to have a low refractive index more reliably.

[0022] The cross sections S1 and S2 are typically cross sections formed by cutting the low refractive index film 10 along a plane parallel to the normal to the surface of the substrate 20. The cross sections shown in the cross sections in the accompanying drawings or the electron microscope photographs correspond to such cross sections.

[0023] The first layer 11 and the second layer 12 are distinguished by an interface perpendicular to the normal to the surface of the substrate 20. Typically, in the thickness direction of the low refractive index film 10, a portion closer to the substrate 20 than the interface corresponds to the first layer 11, and a portion farther from the substrate 20 than the interface corresponds to the second layer 12. The interface may be real or virtual. For example, the binder 14 may form a continuous phase in the first layer 11 and the second layer 12.

[0024] The low refractive index film 10 has a thickness dt of, for example, 70 nm or more. When the thickness d1 of the first layer 11 is, for example, 70 nm ≤ dt ≤ 400 nm, it is equal to dt / 2. Also, when the thickness d1 of the first layer 11 is, for example, 400 nm < dt, it is equal to 200 nm. By the first layer 11 having such a thickness and satisfying at least one of the conditions (I) and (II), the low refractive index film 10 is more likely to surely exhibit high antireflection performance.

[0025] The refractive index of the low refractive index film 10 is desirably 1.05 or more and 1.28 or less, and more desirably 1.10 or more and 1.25 or less.

[0026] The material of the binder 14 is not limited to a specific material. The material of the binder 14 is, for example, a material that satisfies desired properties from viewpoints such as environmental resistance, abrasion resistance, and adhesion to the substrate. Also, the material of the binder 14 is desirably a material having high transparency with respect to light in a predetermined wavelength range used in an article provided with the low refractive index film 10. The predetermined wavelength range used in the article provided with the low refractive index film 10 may exist in the visible light region or the near infrared region.

[0027] The binder 14 contains, for example, silica, silsesquioxane, or a mixture of silica and silsesquioxane. In this case, in the binder 14, the wavelength range in which transparency can be ensured in the visible light region is likely to become wide. In addition, it is also possible to lower the refractive index of the binder 14 to some extent.

[0028] The binder 14 may contain a predetermined curable resin, for example, according to the type of the substrate 20 or the performance required for the article provided with the low refractive index film 10. The curable resin is liquid when applied to the surface of the substrate 20, but hardens by methods such as heating and light energy irradiation after application, so the production of the low refractive index film 10 is likely to be facilitated. Examples of the curable resin are phenol resin, epoxy resin, melamine resin, unsaturated polyester resin, polyurethane resin, polyimide resin, acrylic resin, and silicone-based resin.

[0029] When the binder 14 includes silica, silsesquioxane, or a mixture of silica and silsesquioxane, for example, 1%≦W Si ≦60% and 5%≦W Sq At least one of the conditions ≦90% is met. Si is the ratio of the mass of silica contained in the binder 14 to the mass of the solid content of the low refractive index film 10. Sq is the ratio of the mass of the silsesquioxane contained in the binder 14 to the mass of the solid content of the low refractive index film 10. Si ≦60% and 8%≦W Sq At least one of the conditions of 8%≦W Si ≦30% and 10%≦W Sq At least one of the conditions ≦60% is met.

[0030] When the binder 14 contains silica, silsesquioxane, or a mixture of silica and silsesquioxane, for example, the condition 5%≦Wb≦90% is satisfied. Wb is the ratio of the sum of the mass of silica and the mass of silsesquioxane contained in the binder 14 to the mass of the solid content of the low refractive index film 10. Desirably, the condition 10%≦Wb≦85% is satisfied, and more desirably, the condition 20%≦Wb≦80% is satisfied. The silica in the binder 14 is obtained, for example, by hydrolysis and condensation polymerization of a tetrafunctional alkoxysilane. The silsesquioxane in the binder 14 is obtained, for example, by hydrolysis and condensation polymerization of a trifunctional alkoxysilane.

[0031] The hollow particles 13 are typically particles having holes partitioned by a shell. When the low refractive index film 10 contains the hollow particles 13, the refractive index of the low refractive index film 10 tends to be low.

[0032] Average particle diameter d of hollow particles 13 e is not limited to a specific value. The average particle diameter d e is, for example, 20 nm or more and 100 nm or less. eWhen the average particle diameter d is 20 nm or more, the pores inside the hollow particles 13 tend to have a desired volume. This tends to lower the refractive index of the low refractive index film 10. e Since the average particle diameter d of the hollow particles 13 is 100 nm or less, light scattering is unlikely to become large. e is, for example, the average particle diameter in the number-based particle size distribution.

[0033] Average particle diameter d of hollow particles 13 e is preferably 25 nm or more and 90 nm or less, and more preferably 30 nm or more and 80 nm or less.

[0034] The material of the shell of the hollow particle 13 is not limited to a specific material. Examples of the material of the shell of the hollow particle 13 include inorganic compounds such as SiO2, ZrO2, and MgF2, fluorine-based compounds such as polytetrafluoroethylene (PTFE) and tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), and resinous polymers. The material of the shell of the hollow particle 13 desirably has a low refractive index, for example, a refractive index equal to or lower than that of SiO2.

[0035] The shell thickness of the hollow particle 13 is not limited to a specific value. The shell thickness of the hollow particle 13 is, for example, 5 nm or more and 20 nm or less, and preferably 10 nm or more and 20 nm or less.

[0036] The ratio Whp [%] of the mass of the hollow particles 13 to the mass of the solid content of the low refractive index film 10 is not limited to a specific value. The ratio Whp is, for example, 5% to 90%, preferably 10% to 85%, and more preferably 20% to 80%.

[0037] The relationship between the content of the hollow particles 13 and the content of the binder 14 in the low refractive index film 10 is not limited to a specific relationship. The low refractive index film 10 satisfies, for example, the condition of 0.2 < Wb / Whp < 20. By satisfying the condition of Wb / Whp < 20, the refractive index of the low refractive index film 10 is likely to be low. In addition, even if the difference between the expansion coefficient of the base material 20 and the expansion coefficient of the low refractive index film 10 is large, it is difficult for cracks or tears to occur in the low refractive index film 10 due to temperature changes. By satisfying the condition of 0.2 < Wb / Whp, the low refractive index film 10 is likely to have a desired mechanical strength, and it can be expected to make it difficult for the low refractive index film 10 to break or peel off.

[0038] The low refractive index film 10 preferably satisfies the condition of 0.3 < Wb / Whp < 15, more preferably satisfies the condition of 0.4 < Wb / Whp < 12, and even more preferably satisfies the condition of 0.5 < Wb / Whp < 10.

[0039] The low refractive index film 10 may contain a functional component such as a light absorber as needed. Thereby, the low refractive index film 10 can exhibit an additional function corresponding to the functional component. Examples of the light absorber are an ultraviolet absorber and an infrared absorber. The ultraviolet absorber is not limited to a specific ultraviolet absorber. Examples of the ultraviolet absorber are a benzophenone-based ultraviolet absorber, a benzotriazole-based ultraviolet absorber, and a triazine-based ultraviolet absorber. Examples of the infrared absorber are not limited to a specific infrared absorber. Examples of the infrared absorber are a squarylium-based infrared absorber, a diimonium-based infrared absorber, a cyanine-based infrared absorber, a phthalocyanine-based infrared absorber, an azo-based infrared absorber, and a phosphoric acid-metal compound containing a phosphoric acid derivative such as phosphonic acid and phosphate ester and a metal component such as copper.

[0040] As shown in FIG. 1, for example, a laminate 1a including the low refractive index film 10 can be provided. The laminate 1a includes a base material 20 and a low refractive index film 10. In the laminate 1a, the low refractive index film 10 is formed along the surface of the base material 20.

[0041] The low refractive index film 10 is in contact with the surface of the substrate 20, for example.

[0042] 1, in the laminate 1a, the low refractive index film 10 is formed, for example, in contact with one main surface of the substrate 20. The low refractive index film 10 may be formed, for example, in contact with both main surfaces of the substrate 20.

[0043] The substrate 20 may be a plate-like member having a flat surface, a member such as a lens having a curved surface, a member such as a diffraction grating having an uneven surface, or a member such as a microlens array or diffuser having a surface with fine unevenness. The substrate 20 may be a member having a surface defined by a combination of these surfaces.

[0044] The substrate 20 is an article or a part of an article coated with a low refractive index film or an anti-reflection film, but is not limited to an article having a specific function. The substrate 20 may be, for example, a lens, a mirror, a prism, a diffuser, a flat microlens array, a polarizer, a diffraction grating, a hologram, an optical modulation element, an optical deflection element, and an optical element such as a filter (including an acousto-optical element), a solid-state imaging device, a window or windshield of a building or an automobile, a helmet, a light-transmitting shield such as goggles, and a display device such as a display and a screen. When the low refractive index film 10 is used for anti-reflection, the light transmittance in the laminate 1a is likely to be high.

[0045] As shown in FIG. 1, the base material 20 includes a plate-shaped substrate 21 having, for example, two main surfaces facing opposite each other. The material of the substrate 21 is not limited to a specific material. The material of the substrate 21 is, for example, glass, resin, or a semiconductor material such as silicon. Examples of glass include soda glass, borosilicate glass, aluminoborosilicate glass, fluorophosphate glass, phosphate glass, and multi-component optical glass with enhanced optical properties such as refractive index. Examples of resin include polyolefin-based resins, polycarbonate-based resins, polyamide-based resins, epoxy-based resins, acrylic-based resins, polyether-based resins, polyimide-based resins, polyurethane-based resins, and silicone-based resins.

[0046] The arithmetic mean roughness Ra of the surface of the substrate 20, determined according to the Japanese Industrial Standards (JIS) B 0601-1994, is not limited to a specific value. The arithmetic mean roughness Ra of the surface of the substrate 20 is, for example, 0.3 nm or more and 140 nm or less. When the arithmetic mean roughness Ra of the surface of the substrate 20 is 0.3 nm or more, the adhesion between the substrate 20 and the low refractive index film 10 is likely to be good. Therefore, even if the first layer 11 has voids 15, the low refractive index film 10 is unlikely to peel off from the substrate 20. When the arithmetic mean roughness Ra of the surface of the substrate 20 is 140 nm or less, the film thickness of the low refractive index film 10 is unlikely to vary spatially, and the function that the low refractive index film 10 should exhibit is unlikely to vary in-plane. In addition, it is possible to prevent the effective light transmission performance from decreasing due to phenomena such as light scattering in the laminate 1a.

[0047] The arithmetic mean roughness Ra of the surface of the substrate 20 is preferably 0.4 nm or more and 100 nm or less, more preferably 0.5 nm or more and 50 nm or less, and even more preferably 0.5 nm or more and 35 nm or less.

[0048] The arithmetic mean roughness Ra of the surface of the substrate 20 and the wavelength λ of the light incident on the laminate 1a i [nm] is, for example, Ra≦λ i / 4. This makes it difficult for light to be scattered in the laminate 1a. For example, when the incident light is visible light having a wavelength of 550 nm, the relationship Ra≦550 / 4[nm]=137.5 nm is satisfied, so that a decrease in transmittance due to light scattering can be prevented.

[0049] The arithmetic average roughness Ra of the surface of the substrate 20 and the average particle diameter d of the hollow particles 13 e For example, Ra≦d e This makes it easy for the hollow particles 13 to be uniformly dispersed in the low refractive index film 10. For example, the average particle diameter d e When is 50 nm, the relationship Ra≦50 nm is preferably satisfied.

[0050] The contact angle α of the water droplet on the surface of the substrate 20 is not limited to a specific value. On the other hand, by adjusting the wettability of the surface of the substrate 20, voids 15 are easily formed in the low refractive index film 10 near the interface between the low refractive index film 10 and the substrate 20.

[0051] The contact angle α of the water droplet on the surface of the substrate 20 is, for example, 5° or more and 140° or less. When the contact angle α is 5° or more, the liquid composition, which is the precursor of the low refractive index film 10, is repelled from the surface of the substrate 20, and the voids 15 can be formed in the first layer 11 in a desired state. When the contact angle α is 140° or less, the liquid composition, which is the precursor of the low refractive index film 10, can be prevented from being excessively repelled from the surface of the substrate 20, and the low refractive index film 10 is likely to have a desired film thickness. In addition, streaky defects and film thickness variations are unlikely to occur in the low refractive index film 10, and the low refractive index film 10 is likely to exhibit uniform characteristics within its surface.

[0052] The arithmetic mean roughness Ra of the surface of the substrate 20 and the contact angle α of the water droplet on the surface of the substrate 20 are adjusted, for example, by subjecting the surface of the substrate 20 to a predetermined surface treatment. An example of the surface treatment method is a method of chemically or physically changing the surface state of the substrate 20 using a chemical treatment or a blasting treatment. For example, according to a method of forming fine irregularities on the surface of the substrate 20, the liquid composition, which is a precursor of the low refractive index film 10, on the surface of the substrate 20 is likely to exhibit a physical adhesive effect such as an anchor effect. An example of the surface treatment method may be a method of changing the state of chemical bonds of functional groups on the surface of the substrate 20, such as a corona treatment, a plasma treatment, an ultraviolet irradiation treatment, and a flame treatment. Such a method can also adjust the wettability of the liquid composition, which is a precursor of the low refractive index film 10 on the surface of the substrate 20. In addition, the wettability of the liquid composition, which is a precursor of the low refractive index film 10 on the surface of the substrate 20, may be adjusted by applying a surface treatment agent such as a primer or a silane coupling agent. In addition, the arithmetic mean roughness Ra of the surface of the substrate 20 and the contact angle α of a water droplet on the surface of the substrate 20 may be adjusted by forming the surface of the substrate 20 with predetermined layers such as a functional layer and an underlayer.

[0053] The substrate 20 may have a predetermined functional layer. In this case, the functional layer is, for example, a layer, film, or film-like layer that adjusts the transmittance and reflectivity of light, such as an anti-reflection film, a light absorbing film, and a light reflecting film. The anti-reflection film is, for example, a single-layer or multi-layer dielectric film containing an inorganic material such as SiO2, MgF2, and TiO2. The light reflecting film is, for example, a single-layer or multi-layer dielectric film containing an inorganic material such as SiO2, MgF2, and TiO2. The light reflecting film may be a metal film. The light absorbing film is, for example, a film containing a resin containing an infrared absorbing agent or an ultraviolet absorbing agent. Examples of infrared absorbing agents are squarylium-based dyes, diimmonium-based dyes, cyanine-based dyes, phthalocyanine-based dyes, azo-based dyes, and complexes containing phosphorus-containing oxides and metals such as copper. Examples of ultraviolet absorbing agents are benzophenone-based dyes, benzotriazole-based dyes, and triazine-based dyes. The functional layer may be a layer, membrane, or film-like layer that adjusts the behavior of the film against moisture or oil contained in the environment, such as an anti-fogging film, a water-repellent film, an oil-repellent film, or a hydrophilic film.

[0054] The low refractive index film 10 can be produced, for example, by applying a predetermined liquid composition to the surface of the substrate 20 to form a coating film, and then curing the coating film. The liquid composition can be prepared, for example, by mixing the raw material of the binder 14 with the hollow particles 13. The above-mentioned functional components are added to the liquid composition as necessary.

[0055] The liquid composition may contain, for example, a solvent and water. This makes it easier to achieve the objectives of adjusting the viscosity of the liquid composition, improving the dispersibility of the functional component in the liquid composition, or improving the solubility of the raw material of the binder 14. The solvent is not limited to a specific solvent. Examples of the solvent may be tetrahydrofuran (THF), cyclohexanone, cyclohexane, toluene, xylene, alcohols, phenols, water, glycerin, acetone, methyl ethyl ketone (MEK), diethyl ether, ethyl acetate, and mixtures thereof.

[0056] The liquid composition may contain, for example, an acid. When the raw material of the binder 14 contains an alkoxysilane, the acid acts as a catalyst for a reaction such as hydrolysis of the alkoxysilane. The acid is not limited to a specific acid. Examples of the acid include formic acid and hydrochloric acid.

[0057] The laminate 1a can be modified from various viewpoints. For example, the laminate 1a may be formed as the laminate 1b shown in FIG. 2A, the laminate 1c shown in FIG. 2B, the laminate 1d shown in FIG. 2C, or the laminate 1e shown in FIG. 2D. Each of the laminates 1b, 1c, 1d, and 1e is configured similarly to the laminate 1a, except for the parts that are particularly described. The components of the laminate 1b, 1c, 1d, or 1e that are the same as or correspond to the components of the laminate 1a are given the same reference numerals, and detailed description is omitted. The description of the laminate 1a also applies to the laminate 1b, 1c, 1d, and 1e, unless technically inconsistent.

[0058] 2A and 2B, the substrate 20 of the laminates 1b and 1c further includes an underlayer 22. The underlayer 22 forms the surface of one or both main surfaces of the substrate 20. In the laminate 1b, the low refractive index film 10 is formed on the underlayer 22. The underlayer 22 makes it easy to adjust the surface of the substrate 20 to a state suitable for forming the low refractive index film 10. For example, the arithmetic mean roughness Ra of the surface of the substrate 20 or the contact angle α of a water droplet on the surface of the substrate 20 can be easily adjusted to a desired range.

[0059] In the laminate 1c, a pair of low refractive index films 10 are formed on both main surfaces of a substrate 20. One of the pair of low refractive index films 10 is formed on an underlayer 22.

[0060] The underlayer 22 is not limited to a specific layer. The underlayer 22 includes, for example, at least one of silica and silsesquioxane. The underlayer 22 may include silica, silsesquioxane, or a mixture thereof. The underlayer 22 may include an inorganic material such as SiO2, TiO2, or MgF2. The underlayer 22 may be a multilayer film in which a plurality of layers of the inorganic material are laminated. The underlayer 22 may be a layer including a resin such as a polyolefin resin, a polycarbonate resin, a polyamide resin, an epoxy resin, an acrylic resin, a polyether resin, a polyimide resin, a polyurethane resin, a fluorine resin, or a silicone resin.

[0061] 2A and 2B, one of the main surfaces of the substrate 20 is formed by the underlayer 22. On the other hand, both of the main surfaces of the substrate 20 may be formed by the underlayer 22. In this case, a pair of low refractive index films 10 may be formed on the underlayer 22 that forms both of the main surfaces of the substrate 20.

[0062] The thickness of the underlayer 22 is not limited to a particular thickness, and the underlayer 22 has a thickness of, for example, 5 to 50 nm.

[0063] As shown in FIG. 2C and FIG. 2D, the substrate 20 of the laminates 1d and 1e further includes a functional layer 23. The functional layer 23 forms the surface of one of the main surfaces of the substrate 20. In the laminate 1d, the low refractive index film 10 is formed on the functional layer 23. The functional layer 23 can impart a desired function to the laminates 1d and 1e. In addition, the functional layer 23 can adjust the surface of the substrate 20 to a state suitable for forming the low refractive index film 10. For example, the functional layer 23 can easily adjust the arithmetic mean roughness Ra of the surface of the substrate 20 or the contact angle α of a water droplet on the surface of the substrate 20 to a desired range.

[0064] In the laminate 1e, a pair of low refractive index films 10 are formed on both main surfaces of a substrate 20. One of the pair of low refractive index films 10 is formed on a functional layer 23.

[0065] The functional layer 23 is not limited to a specific layer as long as it has a predetermined function. The functional layer 23 is, for example, a layer, film, or film-like layer that adjusts the transmittance and reflectivity of light, such as an anti-reflection film, a light absorbing film, and a light reflecting film. The anti-reflection film is, for example, a film consisting of a single layer or multiple layers containing inorganic materials such as SiO2, MgF2, and TiO2. The light reflecting film may be, for example, a film consisting of a single layer or multiple layers containing inorganic materials such as SiO2, MgF2, and TiO2, or a metal film composed of a metal. The light absorbing film is, for example, a film containing a resin containing an infrared absorbing agent or an ultraviolet absorbing agent. Examples of the infrared absorbing agent are squarylium-based dyes, diimmonium-based dyes, cyanine-based dyes, phthalocyanine-based dyes, azo-based dyes, and complexes containing phosphorus-containing oxides and metals such as copper. Examples of the ultraviolet absorbing agent are benzophenone-based dyes, benzotriazole-based dyes, and triazine-based dyes. The light absorbing film may include a metal film composed of a metal.

[0066] The functional layer 23 may be a layer, film, or film that adjusts the behavior of the functional layer 23 with respect to moisture or oil contained in the environment, such as an anti-fogging film, a water-repellent film, an oil-repellent film, or a hydrophilic film. In other words, the laminates 1d and 1e may include a substrate 20, at least one of an anti-fogging film, a water-repellent film, an oil-repellent film, and a hydrophilic film formed on the substrate 20, and a low refractive index film 10.

[0067] 2C and 2D, the surface of one of the main surfaces of the substrate 20 is formed by the functional layer 23. On the other hand, the surfaces of both main surfaces of the substrate 20 may be formed by the functional layer 23. In this case, the low refractive index film 10 may be formed on each of the functional layers 23 forming the surfaces of both main surfaces of the substrate 20.

[0068] Various articles including the low refractive index film 10 can be provided. For example, an optical element having a surface formed by the low refractive index film 10 can be provided. A windbreak material including the low refractive index film 10 can also be provided. Examples of windbreak materials are window glass and windshields. Furthermore, a display device including the low refractive index film 10 can also be provided. EXAMPLES

[0069] The present invention will be described in more detail with reference to examples. Note that the present invention is not limited to the following examples. First, the evaluation methods for each example and each comparative example will be described.

[0070] <Evaluation of film-forming properties> The film-forming properties of the liquid composition for low refractive index film according to each Example and Comparative Example on the surface of the substrate according to each Example and Comparative Example were evaluated. When it was confirmed that there were areas where the liquid composition for low refractive index film was not applied to the surface of the substrate when it was applied, or that the thickness of the low refractive index film was uneven, the film-forming properties were evaluated as "F". On the other hand, when these were not confirmed, the film-forming properties were evaluated as "A". The results are shown in Table 2.

[0071] <Reflectance, refractive index, and film thickness> Using a spectrophotometer (Hitachi High-Technologies Corporation, product name: U-4000), the incident angle was adjusted to 12°, and the spectral reflectance of the laminate according to each Example and Comparative Example was measured. Furthermore, the refractive index and film thickness of the low refractive index film according to each Example and Comparative Example were determined using optical thin film design software FilmWizard (Scientific Computing International). The spectral reflectance, refractive index, and film thickness at the D line (wavelength 589 nm) are shown in Table 2. In addition, as a laminate for measuring the spectral reflectance, when a low refractive index film is formed on one main surface of a substrate, a laminate can be used in which the influence of reflection by the main surface can be ignored by painting the entire main surface on which the low refractive index film is not formed with black, making it a rough surface, or making it a matte surface. In this case, the black paint is not limited to a specific paint, but may be black paint or a paint used in the optical field called flare cut. As the black paint, for example, GT-1000, GT-2000, GT-7, and CS-37 manufactured by Canon Chemicals can be used. The matte surface was formed, for example, by using an abrasive having a grain size of #500 (500th number) or more. The main surface processed into a matte surface may then be painted black. When the laminate includes an underlayer, the thickness of the underlayer was measured by reflection spectroscopy using a film thickness measurement system F20-UV manufactured by Filmetrics before the formation of the low refractive index film.

[0072] <Haze> Using a haze meter (manufactured by Suga Test Instruments, product name: HZ-V3), the haze of each of the laminates according to the examples and comparative examples was measured at three points 1 cm apart, and the average value was calculated and used as the haze of each of the examples and comparative examples. The results are shown in Table 2.

[0073] <Number of voids Nv and void fraction Vv1> To confirm the void state in the low refractive index film of the laminate according to each example and each comparative example, first, a 100 nm-thick sample was cut out along a cross-section parallel to the normal on the surface of the substrate using a convergent ion beam apparatus SMI3200F manufactured by SII NanoTechnology Inc. Carbon with a thickness of 400 to 500 nm was deposited on the outermost surface to prepare a sample. The cross-section of this sample was subjected to bright-field transmission observation at a magnification of 250,000 times using a scanning transmission electron microscope (STEM) S-5500 manufactured by Hitachi High-Technologies Corporation, and a transmission photograph image of the laminate including the low refractive index film was obtained. The acceleration voltage was 200 kV. In the transmission photograph image of the laminate, voids were observed with white enhancement. After digitizing the obtained transmission photograph image of the cross-section of the laminate in gradations from 0 to 255, histogram equalization processing was performed to obtain an image with a certain contrast. Then, gradations from 229 to 255 were defined as voids. The number, number density, and cross-sectional area of the voids were calculated as follows. First, for the transmission photograph image of the cross-section of the laminate, a 1000 nm (1 μm) image was obtained along the direction parallel to the surface of the substrate, and voids were specified based on the above method. Fig. 4 shows the transmission photograph image of the cross-section of the laminate and the figure of the specified voids. In Fig. 4, the voids are shown in black for easy distinction from other parts. Next, the thickness dt of the low refractive index film was measured to obtain the thickness d1 of the first layer, and the area At1 of the cross-section S1 of the first layer was obtained by the calculation of d1 × 1000. The thickness d1 of the first layer is d1 = dt / 2 when 70 nm ≤ dt ≤ 400 nm, and d1 = 200 nm when 400 nm < dt. Among the voids included in the cross-section S1 of the first layer, the number Nv1 of voids with a cross-sectional area of 1000 nm 2 or more was counted, and the sum Av1 of the cross-sectional areas of voids with a cross-sectional area of 1000 nm 2 or more was calculated. Similarly, the area At2 (= (dt - d1) × 1000) of the cross-section S2 of the second layer was calculated, and among the voids included in the cross-section S2 of the second layer, the number Nv2 of voids with a cross-sectional area of 1000 nm 2 or more was counted, and the sum of the cross-sectional areas of voids with a cross-sectional area of 1000 nm 2The sum Av2 of the cross-sectional areas of the above voids was calculated. The number Nv1 of the voids was divided by the area At1 to obtain the number density ρv1. In addition, the sum Av1 of the cross-sectional areas of the voids was divided by the area At1 to determine the void fraction Vv1. In each example, a transmission image of the laminate was obtained at three points spaced 10 mm apart in the plane, and the above parameters were calculated and their average values ​​were used. The values ​​of the number Nv of voids and the area ratio Vv [%] of the voids were rounded down to the nearest whole number. The above calculations, etc., were performed, if necessary, using ImageJ version 1.51, an image processing software provided by the National Institutes of Health.

[0074] <Wear resistance test> Asahi Kasei Chemicals cotton cloth Clint 50g / cm 2 The surface of the laminate was reciprocated five times while a load of 10 ... D But, ΔR D / (D-ray reflectance R before abrasion resistance test D )≦25% is evaluated as "A", and ΔR D / (D-ray reflectance R before abrasion resistance test D )>25% of cases were rated as "F".

[0075] <Example 1> 0.6 g of tetraethoxysilane (TEOS) (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3 mass% formic acid (manufactured by Kishida Chemical Co., Ltd.), 3 g of hollow silica particle-containing sol (manufactured by JGC Catalysts and Chemicals, product name: Sururia 4110), and 22.4 g of ethanol (manufactured by Kishida Chemical Co., Ltd.) were mixed and reacted at 35°C for 3 hours. The hollow silica particle-containing sol used contained a solvent and contained 25 mass% hollow silica as a solid content, and the average particle diameter of the hollow silica particles in the particle size distribution based on the number was about 50 nm. The thickness of the shell made of silica of the hollow silica particles was 10 to 20 nm. The maximum dimension of the internal space of the hollow silica particles was about 10 to 30 nm. The refractive index of the hollow particles was 1.25. In this way, a liquid composition for a low refractive index film according to Example 1 was obtained. In the liquid composition for low refractive index film according to Example 1, the content of solid content derived from TEOS was 0.6 mass% in terms of silica, the content of methylsilsesquioxane (MeSq) which is a solid content derived from MTES was 1.6 mass%, and the content of hollow silica particles was 2.6 mass%. In the solid content of the liquid composition for low refractive index film according to Example 1, 13% of silica derived from TEOS, 33% of MeSq derived from MTES, and 54% of hollow silica particles were contained on a mass basis. The content of hollow silica particles was calculated on the assumption that the solid content of the hollow silica particle-containing sol was 25 mass%, and that the solid content was hollow silica particles. In addition, the ratio of the substance amount of MTES to the substance amount of TEOS added in the preparation of the liquid composition for low refractive index film according to Example 1 was 7 / 3.

[0076] A glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, double-sided polished, refractive index: 1.52) made of soda lime glass was washed in ultrapure water for 15 minutes using an ultrasonic cleaner (manufactured by Emerson Japan, model number: Bransonic 5510-J-DTH, output: 135 W). The glass substrate was then washed in a commercially available alkaline cleaning solution (2% dilution of Semiclean LGL, manufactured by Yokohama Yushi Kogyo Co., Ltd.) for 15 minutes, and then washed in ultrapure water for 15 minutes. The surface of the glass substrate was then corona-treated at an output of 14 kV using a corona surface treatment device (manufactured by Shinko Electric Instrumentation Co., Ltd., model number: Corona Master PS-1M). The contact angle of a water droplet on the surface of the glass substrate after the corona treatment was 2°. The glass substrate was stored for 12 hours in a clean bench of less than class 100 maintained at a temperature of 23 to 25°C and a relative humidity of 50 to 60%. In this manner, a substrate according to Example 1 was produced. As shown in Table 1, the contact angle of a water droplet on the surface of the substrate according to Example 1 was 32°, and the arithmetic mean roughness Ra of the surface of the substrate according to Example 1 was 0.5 nm. The contact angle of the water droplet was measured using a contact angle meter manufactured by Asumi Giken Co., Ltd. The arithmetic mean roughness Ra was determined in accordance with JIS B 0601-1994 based on the measurement results using an electron force microscope SPI3700 manufactured by Seiko Denshi Co., Ltd. in cyclic contact mode. This is the same for the other examples and comparative examples.

[0077] The liquid composition for low refractive index film according to Example 1 was applied to one main surface of the substrate according to Example 1 by spin coating to form a coating film. The coating film had a good and uniform appearance. Thereafter, the substrate on which the coating film was formed was placed in an oven maintained at 200°C for 10 minutes, and the coating film was dried to obtain a low refractive index film according to Example 1. This resulted in a laminate according to Example 1 including a substrate and a low refractive index film formed on the substrate. When the appearance of the low refractive index film according to Example 1 was observed, it had a uniform thickness. The surface of the substrate on which the low refractive index film of the laminate according to Example 1 was not formed was ground to a matte surface, and then the spectral reflectance was measured. The reflectance of the laminate according to Example 1 at the D line (wavelength 589 nm) was 0.53%, the film thickness of the low refractive index film according to Example 1 was 121 nm, and the refractive index was determined to be 1.16. In the low refractive index film of Example 1, the masses of the silica and silsesquioxane that form the binder and the hollow silica particles were calculated assuming that they were equal to the masses of the corresponding components contained in the solid content of the liquid composition of Example 1. The results are shown in Table 2.

[0078] <Example 2> Except for the following points, the liquid composition for low refractive index film according to Example 2 was prepared in the same manner as in Example 1. On the assumption that the ratio of the mass of each component to the total mass of the solid content of the liquid composition for low refractive index film is equal to the ratio of the mass of each component to the mass of the low refractive index film, the amounts of TEOS, MTES, and hollow silica particle-containing sol added were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.

[0079] 0.6 g of tetraethoxysilane (TEOS) (manufactured by Tokyo Chemical Industry Co., Ltd.), 1.18 g of methyltriethoxysilane (MTES) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.82 g of 0.3 mass% formic acid (manufactured by Kishida Chemical Co., Ltd.), and 22.4 g of ethanol (manufactured by Kishida Chemical Co., Ltd.) were mixed and reacted for 3 hours at 35° C. Then, ethanol was added to this liquid to adjust the total solid content of TEOS-derived silica and MTES-derived methylsilsesquioxane (MeSq) to 3 mass%, thereby obtaining a liquid composition B for undercoat layer.

[0080] The liquid composition B for underlayer was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form an underlayer B2. A substrate according to Example 2 was obtained. The thickness of the underlayer B2 was 13 nm. The contact angle of a water droplet on the surface of the underlayer B2 was 45°, and the arithmetic mean roughness Ra of the surface of the underlayer B2 was 17 nm.

[0081] The liquid composition for low refractive index film according to Example 2 was applied to the surface of the underlayer B2 of the substrate according to Example 2 by spin coating to form a coating film. The coating film immediately after application had a good and uniform appearance. Then, the substrate according to Example 2 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and the low refractive index film according to Example 2 was formed. This resulted in a laminate according to Example 2 including a substrate and a low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film according to Example 2, the low refractive index film according to Example 2 had a uniform thickness. The surface of the substrate on which the low refractive index film of the laminate according to Example 2 was not formed was ground to a matte surface, and then the spectral reflectance was measured. In addition, the thickness of the underlayer B2 was about 10 nm, and the refractive index was almost the same as that of the glass substrate, so it was considered that the underlayer B2 had almost no effect on the reflectance of the laminate. From the obtained spectral reflectance, the reflectance of the laminate at the D line was 0.1% or less, the film thickness of the low refractive index film according to Example 2 was 121 nm, and the refractive index was calculated to be 1.23. The low refractive index film according to Example 2 contained, by mass, 23% silica, 57% silsesquioxane, and 20% hollow silica particles, which serve as a binder.

[0082] <Example 3> Except for the following points, the liquid composition for a low refractive index film according to Example 3 was prepared in the same manner as in Example 1. On the assumption that the ratio of the mass of each component to the total mass of the solid content of the liquid composition for a low refractive index film is equal to the ratio of the mass of each component to the mass of the low refractive index film, the amounts of TEOS, MTES, and hollow silica particle-containing sol added were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.

[0083] The same liquid composition for underlayer B as that of Example 2 was applied by spin coating to both main surfaces of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer B3, thereby obtaining a substrate according to Example 3. The thickness of underlayer B3 was 13 nm. The contact angle of a water droplet on the surface of underlayer B3 was 43°, and the arithmetic mean roughness Ra of the surface of underlayer B3 was 11 nm.

[0084] The liquid composition for low refractive index film according to Example 3 was applied by spin coating to the surface of the underlayer B3 of the substrate according to Example 3 to form a coating film. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate according to Example 3 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and a low refractive index film according to Example 3 was formed. This resulted in a laminate according to Example 3 including a substrate and a low refractive index film formed on the substrate. According to observation of the appearance of the low refractive index film according to Example 3, the low refractive index film according to Example 3 had a uniform thickness. In the same manner as in Example 1, the spectral reflectance of the laminate according to Example 3 was measured, and then each parameter was calculated. The reflectance of the laminate according to Example 3 at the D line was 0.25%, the film thickness of the low refractive index film according to Example 3 was 120 nm, and the refractive index was 1.19. The low refractive index film according to Example 3 contained 19% silica, 51% silsesquioxane, and 30% hollow silica particles, which constitute a binder, by mass.

[0085] <Example 4> A liquid composition for a low refractive index film according to Example 4 was prepared in the same manner as in Example 1, except for the following points. On the assumption that the ratio of the mass of each component to the total mass of the solid content of the liquid composition for a low refractive index film is equal to the ratio of the mass of each component to the mass of the low refractive index film, the amounts of TEOS, MTES, and hollow silica particle-containing sol added were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.

[0086] The same liquid composition for underlayer B as that of Example 2 was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer B4, thereby obtaining a substrate according to Example 4. The thickness of underlayer B4 was 11 nm. The contact angle of a water droplet on the surface of underlayer B4 was 42°, and the arithmetic mean roughness Ra of the surface of underlayer B4 was 13 nm.

[0087] The liquid composition for low refractive index film according to Example 4 was applied to the surface of the underlayer B4 of the substrate according to Example 4 by spin coating to form a coating film. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate according to Example 4 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and a low refractive index film according to Example 4 was formed. This resulted in a laminate according to Example 4 including a substrate and a low refractive index film formed on the substrate. According to observation of the appearance of the low refractive index film according to Example 4, the low refractive index film according to Example 4 had a uniform thickness. In the same manner as in Example 1, the spectral reflectance of the laminate according to Example 4 was measured, and then each parameter was calculated. The reflectance of the laminate according to Example 4 at the D line was 0.62%, the film thickness of the low refractive index film according to Example 4 was 123 nm, and the refractive index was 1.15. The low refractive index film according to Example 4 contained 17% silica, 43% silsesquioxane, and 40% hollow silica particles, which constitute a binder, by mass.

[0088] <Example 5> Except for the following points, the liquid composition for a low refractive index film according to Example 5 was prepared in the same manner as in Example 1. On the assumption that the ratio of the mass of each component to the total mass of the solid content of the liquid composition for a low refractive index film is equal to the ratio of the mass of each component to the mass of the low refractive index film, the amounts of TEOS, MTES, and hollow silica particle-containing sol added were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.

[0089] The same liquid composition for underlayer B as that of Example 2 was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer B5, thereby obtaining a substrate according to Example 5. The thickness of underlayer B5 was 11 nm. The contact angle of a water droplet on the surface of underlayer B5 was 44°, and the arithmetic mean roughness Ra of the surface of underlayer B5 was 16 nm.

[0090] The liquid composition for low refractive index film according to Example 5 was applied by spin coating to the surface of the underlayer B5 of the substrate according to Example 5 to form a coating film. The coating film immediately after application had a good and uniform appearance. Then, the substrate according to Example 5 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and the low refractive index film according to Example 5 was formed. This resulted in a laminate according to Example 5 including the substrate and the low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film according to Example 5, the low refractive index film according to Example 5 had a uniform thickness. After measuring the spectral reflectance of the laminate according to Example 5 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate according to Example 5 at the D line was 1.13%, the film thickness of the low refractive index film according to Example 5 was 121 nm, and the refractive index was 1.12. The low refractive index film according to Example 5 contained 14% silica, 36% silsesquioxane, and 50% hollow silica particles, which constitute a binder, by mass.

[0091] <Example 6> A liquid composition for a low refractive index film according to Example 6 was prepared in the same manner as in Example 1, except for the following points. On the assumption that the ratio of the mass of each component to the total mass of the solid content of the liquid composition for a low refractive index film is equal to the ratio of the mass of each component to the mass of the low refractive index film, the amounts of TEOS, MTES, and hollow silica particle-containing sol added were adjusted so that the ratio of the mass of each component to the mass of the low refractive index film was the value shown in Table 2.

[0092] The same liquid composition for underlayer B as that of Example 2 was applied by spin coating to both main surfaces of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer B6, thereby obtaining a substrate according to Example 6. The thickness of underlayer B6 was 14 nm. The contact angle of a water droplet on the surface of underlayer B6 was 41°, and the arithmetic mean roughness Ra of the surface of underlayer B6 was 12 nm.

[0093] The liquid composition for low refractive index film according to Example 6 was applied by spin coating to the surface of the underlayer B6 of the substrate according to Example 6 to form a coating film. The coating film immediately after application had a good and uniform appearance. Then, the substrate according to Example 6 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and a low refractive index film according to Example 6 was formed. This resulted in a laminate according to Example 6 including a substrate and a low refractive index film formed on the substrate. According to observation of the appearance of the low refractive index film according to Example 6, the low refractive index film according to Example 6 had a uniform thickness. After measuring the spectral reflectance of the laminate according to Example 6 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate according to Example 6 at the D line was 1.50%, the film thickness of the low refractive index film according to Example 6 was 122 nm, and the refractive index was 1.10. The low refractive index film according to Example 6 contained 8% silica, 22% silsesquioxane, and 70% hollow silica particles, which constitute a binder, by mass.

[0094] <Example 7> A liquid composition C for an undercoat layer was obtained by adding 97 g of ethanol to 3 g of n-octyltrichlorosilane (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0095] The liquid composition C for underlayer was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer C7, and a substrate according to Example 7 was obtained. The thickness of underlayer C7 was 13 nm. The contact angle of a water droplet on the surface of underlayer C7 was 64°, and the arithmetic mean roughness Ra of the surface of underlayer C7 was 23 nm.

[0096] The same liquid composition for low refractive index film as that of Example 1 was applied to the surface of the underlayer C7 of the substrate of Example 7 by spin coating to form a coating film. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate of Example 7 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and a low refractive index film of Example 7 was formed. This resulted in a laminate of Example 7 including a substrate and a low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film of Example 7, the low refractive index film of Example 7 had a uniform thickness. After measuring the spectral reflectance of the laminate of Example 7 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate of Example 7 at the D line was 0.45%, the film thickness of the low refractive index film of Example 7 was 119 nm, and the refractive index was 1.17. The low refractive index film of Example 7 contained 13% silica, 33% silsesquioxane, and 54% hollow silica particles, which constitute a binder, by mass.

[0097] <Example 8> A liquid composition D for an undercoat layer was obtained by adding 97 g of ethanol to 3 g of 1H,1H,2H,2H-perfluorooctyltrichlorosilane (manufactured by Tokyo Chemical Industry Co., Ltd.).

[0098] The liquid composition D for underlayer was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form underlayer D8, and a substrate according to Example 8 was obtained. The thickness of underlayer D8 was 11 nm. The contact angle of a water droplet on the surface of underlayer D8 was 118°, and the arithmetic mean roughness Ra of the surface of underlayer D8 was 35 nm.

[0099] The same liquid composition for low refractive index film as that of Example 1 was applied to the surface of the underlayer D8 of the substrate of Example 8 by spin coating to form a coating film. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate of Example 8 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and a low refractive index film of Example 8 was formed. This resulted in a laminate of Example 8 including a substrate and a low refractive index film formed on the substrate. According to observation of the appearance of the low refractive index film of Example 8, the low refractive index film of Example 8 had a uniform thickness. After measuring the spectral reflectance of the laminate of Example 8 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate of Example 8 at the D line was 0.55%, the film thickness of the low refractive index film of Example 8 was 120 nm, and the refractive index was 1.16. The low refractive index film of Example 8 contained 13% silica, 33% silsesquioxane, and 54% hollow silica particles, which constitute a binder, by mass.

[0100] <Example 9> Using an ultrasonic cleaner, a polycarbonate (PC) substrate (manufactured by AS ONE Corporation, product number: PCC0050503, size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.59) was washed in ultrapure water for 15 minutes. Thereafter, the PC substrate was washed with a commercially available alkaline cleaning solution for 15 minutes, and further washed in ultrapure water for 15 minutes. Next, using a corona surface treatment device (manufactured by Shinko Electric Instrumentation Co., Ltd., model number: Corona Master PS-1M) in the same manner and under the same conditions as in Example 1, the surface of the PC substrate was corona-treated for 10 minutes at an output of 14 kV, to obtain a base material according to Example 9. The contact angle of a water droplet on the surface of the PC substrate after the corona treatment was 19°, and the arithmetic mean roughness Ra of the surface of the PC substrate after the corona treatment was 34 nm.

[0101] The same liquid composition for low refractive index film as that of Example 1 was applied to one main surface of the substrate of Example 9 by spin coating. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate of Example 9 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, thereby forming the low refractive index film of Example 9. This resulted in a laminate of Example 9 including the substrate and the low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film of Example 9, the low refractive index film of Example 9 had a uniform thickness. After measuring the spectral reflectance of the laminate of Example 9 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate of Example 9 at the D line was 0.57%, the film thickness of the low refractive index film of Example 9 was 122 nm, and the refractive index was 1.18. The low refractive index film of Example 9 contained 13% silica, 33% silsesquioxane, and 54% hollow silica particles, which constitute a binder, by mass.

[0102] <Example 10> Using an ultrasonic cleaner, the same type of substrate as the PC substrate used in Example 9 was washed in ultrapure water for 15 minutes. The PC substrate was then washed with a commercially available alkaline cleaning solution for 15 minutes, and further washed in ultrapure water for 15 minutes. Next, corona treatment was performed in the same manner and under the same conditions as in Example 1, except that the treatment time was adjusted to 1 minute, to obtain a substrate according to Example 10. The contact angle of a water droplet on the surface of the PC substrate after corona treatment was 37°, and the arithmetic mean roughness Ra of the surface of the PC substrate after corona treatment was 27 nm.

[0103] The same liquid composition for low refractive index film as that of Example 1 was applied by spin coating to one main surface of the substrate of Example 10. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate of Example 10 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, thereby forming the low refractive index film of Example 10. This resulted in the laminate of Example 10 including the substrate and the low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film of Example 10, the low refractive index film of Example 10 had a uniform thickness. After measuring the spectral reflectance of the laminate of Example 10 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate of Example 10 at the D line was 0.73%, the thickness of the low refractive index film of Example 10 was 121 nm, and the refractive index was 1.17. As shown in Table 2, the low refractive index film according to Example 10 contained, by mass, 13% silica forming a binder, 33% silsesquioxane, and 54% hollow silica particles.

[0104] <Example 11> Using an ultrasonic cleaner, a substrate of the same type as the PC substrate used in Example 9 was washed in ultrapure water for 15 minutes. The PC substrate was then washed in a commercially available alkaline cleaning solution for 15 minutes, and further washed in ultrapure water for 15 minutes to obtain a substrate according to Example 11. The contact angle of a water droplet on the surface of the substrate according to Example 11 was 71°, and the arithmetic average roughness Ra of the surface of the substrate according to Example 11 was 21 nm.

[0105] The same liquid composition for low refractive index film as that of Example 1 was applied by spin coating to one main surface of the substrate of Example 11. The coating film immediately after application had a good and uniform appearance. Thereafter, the substrate of Example 11 was placed in an oven maintained at 200°C for 10 minutes to dry the coating film, and the low refractive index film of Example 11 was formed. This resulted in a laminate of Example 11 including the substrate and the low refractive index film formed on the substrate. According to the observation of the appearance of the low refractive index film of Example 11, the low refractive index film of Example 11 had a uniform thickness. After measuring the spectral reflectance of the laminate of Example 11 in the same manner as in Example 1, each parameter was calculated. The reflectance of the laminate of Example 11 at the D line was 0.84%, the thickness of the low refractive index film of Example 11 was 123 nm, and the refractive index was 1.16. As shown in Table 2, the low refractive index film according to Example 11 contained, by mass, 13% silica forming a binder, 33% silsesquioxane, and 54% hollow silica particles.

[0106] <Comparative Example 1> While stirring 99.5g of decamethylcyclopentasiloxane (manufactured by Shin-Etsu Chemical Co., Ltd., product name KF-995), 0.5g of tetrachlorosilane (SiCl4) manufactured by Shin-Etsu Chemical Co., Ltd. was added to the decamethylcyclopentasiloxane to prepare a silica-based undercoat layer composition E1. In addition, while stirring 98g of decamethylcyclopentasiloxane, 2g of heptadecafluorodecyltrichlorosilane (CF3(CF2)7(CH2)2SiCl3) was added to the decamethylcyclopentasiloxane to prepare a undercoat layer composition E2.

[0107] On one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass, which had been pre-cleaned by alkaline cleaning, the undercoat layer composition E1 was applied by flow coating under an environment of 25°C temperature and 30% relative humidity to form a coating film, and the coating film was left standing for one minute in a wet state. Next, the undercoat layer composition E1 was applied on the coating film by flow coating under the same conditions, and the coating was left standing for one minute in a wet state. Next, the undercoat layer composition E2 was applied on the wet coating film of the undercoat layer composition E1 on the surface of the glass substrate by flow coating under the same conditions as above, and the coating was left standing for one minute in a wet state. Next, the excess components of the undercoat layer composition on the surface were completely washed away with ethyl alcohol, and the coating film was naturally dried to form the undercoat layer E14, and a base material according to Comparative Example 1 was obtained. The undercoat layer E14 had water repellency due to the action of the undercoat layer composition E2. In addition, it was confirmed that particulate protrusions and columnar protrusions were formed on the surface of the underlayer E14 by the action of the underlayer composition E1. The thickness of the underlayer E14 was 14 nm. The contact angle of a water droplet on the surface of the underlayer E14 was 157°, and the arithmetic mean roughness Ra of the surface of the underlayer E14 was 43 nm.

[0108] The liquid composition for a low refractive index film according to Comparative Example 1 was applied by spin coating to the surface of the underlayer E14 of the substrate according to Comparative Example 1. However, streaky coating unevenness occurred over the entire surface of the substrate according to Comparative Example 1, and a uniform film was not obtained.

[0109] <Comparative Example 2> Tetraethoxysilane (TEOS) (Tokyo Chemical Industry Co., Ltd.) 0.6g, methyltriethoxysilane (MTES) (Tokyo Chemical Industry Co., Ltd.) 1.18g, 0.3 mass% formic acid (Kishida Chemical Co., Ltd.) 0.82g, silica sol (Nissan Chemical Co., Ltd., product name: Snowtex MP-2040, average particle size: 200nm) 3g, and ethanol (Kishida Chemical Co., Ltd.) 22.4g were mixed and reacted for 3 hours at 35°C. Ethanol was added to this liquid to adjust the total solid content of silica derived from tetraethoxysilane and methylsilsesquioxane (MeSq) derived from methyltriethoxysilane to 5 mass%, and a liquid composition F for undercoat layer was obtained.

[0110] The liquid composition F for underlayer was applied by spin coating to one main surface of a glass substrate (size: 40 mm x 40 mm, thickness: 1 mm, refractive index: 1.52) made of float glass that had been pre-cleaned by alkaline cleaning, to form a coating film. Next, this coating film was dried in an oven at 200°C for 10 minutes to form an underlayer F15, thereby obtaining a substrate according to Comparative Example 2. The thickness of the underlayer F15 was 170 nm. The contact angle of a water droplet on the surface of the underlayer F15 was 52°, and the arithmetic mean roughness Ra of the surface of the underlayer F15 was 150 nm.

[0111] The liquid composition for a low refractive index film according to Comparative Example 1 was applied by spin coating to the surface of the underlayer F15 of the substrate according to Comparative Example 2. However, streaky coating unevenness occurred over the entire surface of the substrate according to Comparative Example 2, and a uniform film was not obtained.

[0112] [Table 1]

[0113] [Table 2]

Claims

1. A low refractive index film having at least a first layer and a second layer adjacent to the first layer, A refractive index of 1.01 or more and 1.30 or less, each of the first layer and the second layer contains hollow particles and a binder; the first layer has a thickness that is half or less than the thickness of the low refractive index film and is 200 nm or less; The first layer is a low refractive index film having voids that satisfy at least one of the following conditions (I) and (II): (I) 1000 nm in the cross section of the first layer 2 The number density of the voids having a cross-sectional area of ​​5 / μm 2 More than 100 / μm 2 The following is the result. (II) The ratio of the cross-sectional area of ​​the void in the cross section to the area of ​​the cross section of the first layer is 5% or more and 70% or less.

2. The first layer satisfies the condition (I) above, 1000 nm at the cross section of the first layer 2 The number density of the voids having a cross-sectional area of ​​1000 nm or more in a cross section of the second layer 2 The low refractive index film according to claim 1 , wherein the number density of the voids having a cross-sectional area of ​​at least 100 nm is greater than or equal to 100 nm.

3. The first layer satisfies the condition (II) above, A low refractive index film as described in claim 1 or 2, wherein the ratio of the cross-sectional area of ​​the void in the cross-section of the first layer to the cross-sectional area of ​​the first layer is higher than the ratio of the cross-sectional area of ​​the void in the cross-section of the second layer to the cross-sectional area of ​​the second layer.

4. The low refractive index film has a thickness dt of 70 nm or more, 4. The low refractive index film according to claim 1, wherein the thickness d1 of the first layer is equal to dt / 2 when 70 nm≦dt≦400 nm, and is equal to 200 nm when 400 nm<dt.

5. The low refractive index film according to any one of claims 1 to 4, wherein the hollow particles have an average particle size of 20 nm or more and 100 nm or less.

6. 5. The low refractive index film according to claim 1, wherein a ratio of the content of the binder to the content of the hollow particles is 0.2 or more and 20 or less on a mass basis.

7. A substrate and a low refractive index film according to any one of claims 1 to 6 are included in the composition, The laminate, wherein the first layer is closer to the substrate than the second layer.

8. 8. The laminate according to claim 7, wherein the arithmetic mean roughness of the surface of the substrate, determined in accordance with Japanese Industrial Standards (JIS) B 0601-1994, is 0.3 nm or more and 140 nm or less.

9. The laminate according to claim 7 or 8, wherein a contact angle of a water droplet on the surface of the substrate is from 5° to 140°.

10. The laminate according to any one of claims 7 to 9, wherein the substrate has an underlayer that forms a surface of the substrate.

11. The laminate of claim 10 , wherein the underlayer comprises at least one of silica and silsesquioxane.

12. The laminate according to claim 10 or 11, wherein the underlayer has a thickness of 5 to 50 nm.

13. A substrate; At least one of an anti-fogging film, a water-repellent film, an oil-repellent film, and a hydrophilic film formed on the substrate; The low refractive index film according to any one of claims 1 to 6, Laminate.

14. An optical element having a surface formed by the low refractive index film according to any one of claims 1 to 6.

15. A windbreak material comprising the low refractive index film according to any one of claims 1 to 6.

16. A display device comprising the low refractive index film according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Process for producing silica based film coated article

    JP1999269657A

  • Antireflecting membrane, optical component using antireflecting membrane, image forming apparatus using antireflecting membrane

    JP2006145709A

  • Antireflection film, image display device having the same, optical recording medium, solar power generation module, and method for forming antireflection film

    JP2009211078A

  • Antireflection film and manufacturing method thereof

    JP2012108320A

  • Coating composition and method of manufacturing antireflection member using the same

    JP2012185413A